CORRELATION BETWEEN LEARNING MOTIVATION AND RESULTS OF STUDENTS OF PENJASORKES IN CLASS XI IPS STUDENTS HIGH SCHOOL 10 PEKANBARU - Nur Azian Safitri; Slamet Slamet; Ali Mandan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The problem in this study is the learning motivation of SMA 10 Pekanbaru students who are still not optimally participating in physical education. The aim to be achieved in this research is to find out whether there is a link between learning motivation and the learning outcomes of physical education in class XI IPS students of SMA Negeri 10 Pekanbaru. The instrument in this research was to use a questionnaire for learning motivation and the results of tests in the middle of the semester. The data analysis technique in this research is to use correlation coefficient. Based on the results of the research described by the author in the previous chapter, it can be concluded that there is a significant relationship between learning motivation (X) and learning outcomes (Y) in class XI IPS students of SMA Negeri 10 Pekanbaru. Based on obtained the largest correlation coefficient rcount = 0.918 of rtable = 0.374, so Ha is accepted. This means that there is a link between learning motivation and learning outcomes, where the provisions are the correlation of a variable with other variables that are determined based on r count over r table. Key Words: Motivation Relations, Learning Outcomes